Reparative plastic surgery for central and medial breast cancer - A. Kh. Ismagilov; R. Sh. Khasanov; A. S. Vanesyan (ABV-press, 2014)
Retrospective analysis of the early and long-term results of surgical treatment in patients with central and medial breast cancer (BC) has revealed that reparative plastic surgery does not make the course of the tumor process worse after radical operations in combination with video-assisted thoracoscopic parasternal lymphatic dissection, and the latter does not in turn yield worse immediate and long-term results of surgical treatment in combination with one-stage repair.